Between Elitism and Populism: A Case for Pluralism in Schooling and Homeschooling. Issue 1 (2nd January 2021) - Maranto, Robert
ABSTRACT: Inherently, populism questions elite values and expertise; thus, populists oppose and usually are opposed by elites. Here, I discuss how American Political Science treats elitism, pluralism, and populism, relying heavily on the U.S. Founders' constitutional approaches limiting the power of factions to impose social and political uniformity. Second, I summarize how these models approach the provision of schooling, particularly school choice including homeschooling. In America, public education practice is dominated by elite bureaucratic experts supporting quasi-monopolistic factory models of schooling and unsupportive of the academic rigor some parents desire. Pluralist education as practiced in certain other nation states and historically may offer greater academic success and social peace through diversity, while enhancing achievement and equity. I use these discussions as foundations to critique Bartholet, who argues for severely restricting homeschooling to empower bureaucratic experts and disempower parents. I find it unlikely that such schemes can be implemented without animus against minority factions, and thus without degrading the social diversity inherent to pluralism.